THE EFFECT OF THE FEDERAL RESERVE INTEREST RATE, UNITED STATES MONEY SUPPLY, GLOBAL GOLD PRICES, AND THE U.S. DOLLAR INDEX ON BITCOIN PRICES FOR THE PERIOD 2017–2026 - Nisrul Irawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to examine the effect of the Federal Reserve interest rate, United States money supply, global gold prices, and U.S. dollar indeks on Bitcoin prices for the period 2017–2026. This study employs an associative research design with a quantitative approach. The data used are secondary data obtained from Federal Reserve Economic Data (FRED) and investing.com. The observation period in this study covers December 2017 to March 2026. The analysis technique used is the Autoregressive Distributed Lag (ARDL) model to analyze both short-run and long-run relationships. The results show that in the short run, the Federal Reserve interest rate and global gold prices have a negative and significant effect on Bitcoin Price. But in the long run, the Federal Reserve interest rate and United States money supply have a positive and significant effect on Bitcoin price. Conversely, the global gold prices have a negative but insignificant effect, while the U.S. dollar index has a negative and significant effect on the Bitcoin price.